Tumor volume delineation: A pilot study comparing a digital positron-emission tomography prototype with an analog positron-emission tomography system - Nguyen, Nghi C.; Vercher-Conejero, Jose; Faulhaber, Peter (World Journal of Nuclear Medicine, 2019)
We evaluated the potential differences of a digital positron-emission tomography (PET) prototype equipped with photon-counting detectors (D-PET, Philips Healthcare, Cleveland, Ohio, USA) in tumor volume delineation compared with the analog Gemini TF PET system (A-PET, Philips). Eleven oncologic patients first underwent clinical fluorodeoxyglucose (FDG) PET/computed tomography (CT) on A-PET. The D-PET ring was then inserted between the PET and CT scanner of A-PET and the patient was scanned for the second time. Two interpreters reviewed the two sets of PET/CT images for image quality and diagnostic confidence. FDG avid lesions were evaluated for volume measured at 35% and 50% of maximum standard uptake value (SUV) thresholds (35% SUV, 50% SUV), and for SUV gradient as a measure of lesion sharpness. Bland–Altman plots were used to assess the agreement between the two PET scans. Qualitative lesion conspicuity, sharpness, and diagnostic confidence were greater at D-PET than that of A-PET with favorable inter-rater agreements. Median lesion size of the 24 measured lesions was 1.6 cm. The lesion volume at D-PET was smaller at both 35% SUV and 50% SUV thresholds compared with that of A-PET, with a mean difference of − 3680.0 mm3 at 35% SUV and − 835.3 mm3 at 50% SUV. SUV gradient was greater at D-PET than at A-PET by 49.2% (95% confidence interval: 34.1%–60.8%). Given the smaller volume definition, coupled with improved conspicuity and sharpness, digital PET may be more robust and accurate in tumor rendering compared with analog PET not only for radiotherapy planning but also in prognostication and systemic treatment monitoring.
Keywords: Digital positron-emission tomography; direct photon counting; fluorodeoxyglucose positron-emission tomography; tumor volume rendering